Community Leadership Experience Guide & Booklet - Burkhart, Tori A. (My University, 2018)
During the fall semester of 2018 and spring semesters of both 2018 and 2019, I served as the Community Leadership Experience (CLE) student coordinator for LEAD 212: Introduction to Leadership Concepts. My role in this position was to create a tangible guide and booklet to create a meaningful and purposeful learning experience for over 600 first-semester freshmen. Through research, collaboration with my faculty supervisor, and reflection, I successfully consolidated all information regarding the CLE into an intentionally designed Cats 4 Cans Best Practices Booklet and CLE Guide for students to utilize throughout their experience. Attached are both the booklet and guide for review. Within both documents are clean and simplistic designs meant to improve upon the reader’s experience as they make their way through the CLE. The Cats 4 Cans Best Practices Booklet includes each step of the project’s process, from outlining the history and purpose behind Cats 4 Cans, to providing students with resources to continue to make progress on food insecurity at K-State, in the Manhattan community, and beyond. The purpose of the CLE Guide is to provide students with a clear idea of the CLE’s guidelines and expectations. It focuses on not only the logistics behind the CLE, but also describes the issue of food insecurity and how the Staley School utilizes appreciative inquiry in order to create a powerful learning experience for each learning community (10-12 students) in LEAD 212. In the fall of 2018, the Cats 4 Cans Best Practices Booklet was introduced to all LEAD 212 sections for them to use as a resource throughout the semester. In comparing teaching evaluations between the fall of 2017 and 2018, we concluded the booklet was a success due to both qualitative and quantitative results describing students’ overall satisfaction with the CLE. Moving forward, we hope to continue making progress on improving upon the CLE for first-semester freshmen by further analyzing these results and making adjustments to both the booklet and guide as necessary. My experience working with LEAD 212 students and my faculty advisor has given me a deeper understanding of structuring curriculum, intentionally designing and organizing documents to better suit students, and ultimately helped me discover the next step I want to take in my future career; higher education.